2003
DOI: 10.1034/j.1600-0722.2003.00041.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lipopolysaccharides on vascular endothelial growth factor expression in mouse pulp cells and macrophages

Abstract: Vascular endothelial growth factor (VEGF), a potent pro-angiogenic factor, might regulate the neovascularization observed in the pulp of teeth with deep caries. The purpose of this in vitro study was to evaluate the effect of bacterial lipopolysaccharides (LPS) on VEGF expression in dental pulp cells. Mouse odontoblast-like cells (MDPC-23) or undifferentiated pulp cells (OD-21) were exposed to 0-20 microg ml-1Escherichia coli LPS or 0-80 microg ml-1Prevotella intermedia LPS. As controls, mouse macrophages or g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 47 publications
3
38
0
4
Order By: Relevance
“…32 The expression of the proangiogenic chemokine, CXCL2, is strongly up-regulated in LTA-stimulated odontoblasts, suggesting that CXCL2 might thus contribute to the increased vascularization by binding to CXCR2 that is highly expressed on endothelial cells. 30 An in vitro study by Bofero et al 33 has revealed that odontoblast-like cells stimulated by LPS up-regulate vascular endothelial growth factor (VEGF) expression suggesting a novel role for odontoblasts in the regulation of pulpal angiogenesis. Up-regulated VEGF synthesis by odontoblasts stimulated with LPS might increase the permeability of existing pulp blood vessels, thus facilitating the process of diapedesis of neutrophils, lymphocytes, and monocytes.…”
Section: 14 Discussionmentioning
confidence: 99%
“…32 The expression of the proangiogenic chemokine, CXCL2, is strongly up-regulated in LTA-stimulated odontoblasts, suggesting that CXCL2 might thus contribute to the increased vascularization by binding to CXCR2 that is highly expressed on endothelial cells. 30 An in vitro study by Bofero et al 33 has revealed that odontoblast-like cells stimulated by LPS up-regulate vascular endothelial growth factor (VEGF) expression suggesting a novel role for odontoblasts in the regulation of pulpal angiogenesis. Up-regulated VEGF synthesis by odontoblasts stimulated with LPS might increase the permeability of existing pulp blood vessels, thus facilitating the process of diapedesis of neutrophils, lymphocytes, and monocytes.…”
Section: 14 Discussionmentioning
confidence: 99%
“…HEK-293T, rat dental pulp MDPC-23, and rat odontoblast OD-21 cells (57) were cultured at 37°C, and mouse odontoblast-like M06-G3 cells (58) were maintained at 33°C, all in 5% CO 2 in Dulbecco's modified Eagle's medium (DMEM) supplemented with 4.5 g/liter glucose, L-glutamine, sodium pyruvate (Cellgro, VA), 10% fetal bovine serum (Atlanta Biologicals, GA), 100 g/ml streptomycin, 100 units/ml penicillin (Gibco, NY), and 250 g/ml amphotericin B (Cellgro, VA). To induce differentiation, medium was further supplemented with 50 g/ml ascorbic acid, 10 mM ␤-glycerophosphate, and 1 ϫ 10 Ϫ7 M dexamethasone (Sigma-Aldrich, St. Louis, MO) for up to 21 days.…”
Section: Methodsmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) is considered a key regulator of vascular permeability and one of the major inducers of angiogenesis (12)(13)(14). VEGF-initiated signals may play a critical role in the development of pulp inflammation because cariogenic bacteria induce VEGF up-regulation in dental pulp cells that express VEGFR2 (15,16).…”
mentioning
confidence: 99%